2021
DOI: 10.1093/trstmh/trab116
|View full text |Cite
|
Sign up to set email alerts
|

Insecticide resistance profiles in malaria vector populations from Sud-Kivu in the Democratic Republic of the Congo

Abstract: Background Insecticide resistance has become a widespread problem causing a decline in the effectiveness of vector control tools in sub-Saharan Africa. In this situation, ongoing monitoring of vector susceptibility to insecticides is encouraged by the WHO to guide national malaria control programmes. Our study was conducted from April to November 2018 in Tchonka (Sud-Kivu, Democratic Republic of the Congo) and reported primary data on the resistance status of Anopheles funestus and Anopheles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 27 publications
3
9
0
Order By: Relevance
“…The L1014S- kdr allele frequency of 0.78 in this dataset from 2017-2019 supports these previous surveys, with evidence for ongoing selection of this allele. One additional study has been performed in Tchonka from April–November, 2018 [ 11 ] indicating almost complete fixation of L1014F- kdr (0.98), which was also consistent with this study’s observations of slightly lower frequencies of this mutation (0.75), which may have risen over time under selection. The predictive association between L1014F- kdr and L1014S- kdr and resistance phenotype (i.e.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…The L1014S- kdr allele frequency of 0.78 in this dataset from 2017-2019 supports these previous surveys, with evidence for ongoing selection of this allele. One additional study has been performed in Tchonka from April–November, 2018 [ 11 ] indicating almost complete fixation of L1014F- kdr (0.98), which was also consistent with this study’s observations of slightly lower frequencies of this mutation (0.75), which may have risen over time under selection. The predictive association between L1014F- kdr and L1014S- kdr and resistance phenotype (i.e.…”
Section: Discussionsupporting
confidence: 88%
“…The predictive association between L1014F- kdr and L1014S- kdr and resistance phenotype (i.e. survival or death following an insecticide bioassay or exposure to a vector control intervention) is not absolute [ 30 ], but both mutations have been proposed to play a larger contributing role in resistance to type I (permethrin) versus type II (alpha-cypermethrin and deltamethrin) pyrethroids [ 31 ], which broadly aligns with observations of lower permethrin susceptibility, compared to deltamethrin or alpha-cypermethrin, in some local vector populations [ 10 , 11 , 14 , 32 ]; it is also important to note that differences in discriminating concentrations of pyrethroids used for resistance monitoring and other coinciding resistance mechanisms may also explain some of these discrepancies [ 33 ]. This study also demonstrated a proportion of An.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…funestus s.l. has been reported from multiple sentinel sites [8], including reduced susceptibility to DDT, deltamethrin and permethrin in Kwilu province [9], Nord-Ubangi [10] and Sud-Kivu provinces [11], and to deltamethrin and DDT in Haut-Uélé province [12]. In Kinshasa, high intensity pyrethroid and organochlorine resistance has been observed, with An.…”
Section: Introductionmentioning
confidence: 99%